Sustainable Development Goal 3: Case Study of using Folk media as a Potent tool in India - Shaika, Shahi; Lal, Ruhi; Jonjua, Mehak (The journal of contemporary issues in business and government, 2021)
This study is an attempt to provide comprehensive information and explore the significance of the role of folk media as a powerful tool towards achieving the Sustainable Development Goal 3 in India. The methodology adopted is the analysis of case studies developed through in-depth interview to show the impact of folk media in attaining the objectives. Communication plays a fundamental role in disseminating information, encouraging participation, and stimulating community action. Any program for development is a failure if the people are treated as mere recipients rather than active participants. Involving people as contributors to change and progress will accelerate the process of development. Third world countries like India have been facing odd situations in terms of poverty, environment, health, politics, and education. There have been efforts by the government and non- government agencies to sensitize the citizens and to make them acknowledge the programs intended at improving their socio-economic welfare. Communication is a vital tool in mobilizing people in the direction of the participatory process which in turn makes development an achievable goal. Traditional folk media forms have a personal appeal as they are close to the minds and hearts of the people. Folk arts like Tamasha, Nautanki, Puppetry, Bhand Pather have been used time and again to instruct the masses and bring about a change. The common denominator of communication and development is participation, hence traditional folk media forms can be used effectively for development as they work on the Participatory model.